1973
DOI: 10.1037/h0034212
|View full text |Cite
|
Sign up to set email alerts
|

Ingroup norms and self-identity as determinants of discriminatory behavior.

Abstract: Two studies were undertaken to investigate the relative contribution of race and belief factors in social interaction involving the actual presence of majority (group consensus) and minority (a potential ally) group members. Results showed that under exposure to informational influence from their ingroup, prejudiced subjects discriminated against blacks on tasks dealing with selfidentity (personal reality), an effect which was magnified under conditions of ingroup surveillance with threat of censure. As predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In this study, we examined women's tendency to distance themselves socially from lesbians in a conceptual replication of Boyanowsky and Allen's (1973) study. More specifically, we examined the impact of sexual orientation of a female dissenter on heterosexual women's answers to three types of questions.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, we examined women's tendency to distance themselves socially from lesbians in a conceptual replication of Boyanowsky and Allen's (1973) study. More specifically, we examined the impact of sexual orientation of a female dissenter on heterosexual women's answers to three types of questions.…”
mentioning
confidence: 98%
“…In the same manner, people may differentiate themselves from lesbians by altering the expressions of their opinions, particularly if they hold negative attitudes about lesbians. Boyanowsky and Allen (1973) demonstrated the impact of prejudice on people's willingness to express self-relevant attitudes. They asked participants to express publicly their opinion after they heard either a majority or unanimity express an unpopular opinion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, for example, items assessing friendship choices and adequacy of the models' presentations were influenced more by the race or gender of the model, whereas items assessing perceived similarity to the model were almost exclusively influenced by the belief factor. For adults, race is more likely to influence items tapping intimate social distances, personal opinions, or race-relevant content, while belief tends to influence items involving less intimate social distances and general social opinions (excluding racial issues) (e.g., Boyanowski & Allen 1973;Dienstbier 1972;Triandis & Davis 1965). Thus the relative salience of the cues for attitude expression seems to show differing patterns at different developmental levels, though race or gender appears to more heavily influence items tapping affect toward the stimulus individual.…”
Section: Discussionmentioning
confidence: 82%
“…Experiment IV provided evidence that positive prejudice is mamfested m unprejudiced subjects' pubhc expressions but not in their pnvate expressions Thus, positive prejudice appears to be an attempt by unprejudiced subjects to appear egalitarian rather than a general disposition to affimty for black persons expressed by noninvolving reactions Other recent studies report greater favorabihty for blacks than whites on the part of unprejudiced subjects Boyanowsky and Allen (1973) reported that unprejudiced subjects conformed more to a black than to a white confederate Likewise, Weitz (1972), whose sample was generally "hberal," found overfavorability to blacks on both a general and a specific attitudmal measure Finally, Dutton and Lake (1973) found that unprejudiced subjects who had been threatened by false feedback which indicated that they were prejudiced gave more to a black panhandler than unprejudiced subjects who were not threatened This relationship did not hold for a white panhandler As Gaertner (1974) has mdicated in interpreting results such as these, unprej'udiced individuals are invested m maintaining a self-concept of fairmmdedness, and may accomphsh this end by "bending over backwards" m expressing acceptance of blacks Thus, showing more acceptance of blacks than whites may be more to convince self than others (Gaertner, 1974) Results of other studies indicate that while unprejudiced subjects showed extreme friendhness to blacks in some situations they showed "discrimination m situations which lack normative prescriptions because 'wrong domg' here would not be obvious" (Gaertner, 1974, p 8) Gaertner (1973) found that liberals claimed that they would be as likely to help a black person as a white person, but, in fact, when liberals were actually given the opportunity to respond to a phone call for help, they were more likely to help whites than blacks Weitz (1972) found that while some of her unprejudiced subjects expressed "extreme fnendhness" toward blacks in terms of attitudmal expressions, these same subjects were negative toward blacks m terms of voice tone and subtle behaviors Dutton and Lennox (1974) gave unprejudiced subjects false feedback indicating prejudice as in Dutton and Lake (1973) and found that those who subsequently had an opportumty to compensate by donating to a black panhandler were later less wiUing than other threatened subjects to volunteer time to civil nghts The results of Dutton, Weitz and Gaertner suggest a possible link between involving and nomnvolving reactions. In view of these results, it may be that unprejudiced individuals feel the need to compensate whenever they perceive that they have reacted counter to their self-concept of fairmmdedness Positive prejudice expressed in nomnvolving reactions may be a way to "balance the scales," assummg that unprejudiced subjects recognize at some level of consciousness habitual nonacceptance of blacks manifested m their involving reactions Thus, unprejudiced subjects m Expenments III and IV might be thought of as not merely attempting to look egahtanan m showing more acceptance of blacks than whites, but doing so m order to compensate for past expenences of nonacceptance of blacks…”
Section: Summary and Implicationsmentioning
confidence: 82%